Mushroom body‐preferential expression of proteins/genes involved in endoplasmic reticulum Ca2+‐transport in the worker honeybee (Apis mellifera L.) brain. Issue 1 (21st November 2012) - Uno, Y.; Fujiyuki, T.; Morioka, M.; Kubo, T.
Abstract To identify the molecular characteristics specific to the mushroom body (MB, a higher processing centre) neurones in the honeybee brain, we previously used proteomics to identify proteins that are preferentially expressed in these MBs. Here we continued our proteomic analysis to show that reticulocalbin, which is involved in endoplasmic reticulum (ER) Ca2+ transport, is also preferentially expressed in the MBs in the honeybee brain. Gene expression analysis revealed that reticulocalbin is preferentially expressed in the large‐type Kenyon cells, which are MB‐intrinsic neurones. In addition, the gene for the ryanodine receptor, which is also involved in ER Ca2+ transport, was also preferentially expressed in the large‐type Kenyon cells. In contrast, the expression of three other ER‐related genes, protein disulphide isomerase, sec61 and erp60, was not enriched in the MBs. These findings further support the notion that the function of ER Ca2+‐signalling, but not the mere intracellular density of ER, is specifically enhanced in the large‐type Kenyon cells in the honeybee brain.